HEAT – MECHANICALLY INDUCED STRUCTURE DEVELOPMENT IN PARTIALLY CRYSTALLINE POLYESTER FIBERS. INFLUENCE OF THE MECHANICAL STRESS: HEAT – MECHANICALLY INDUCED STRUCTURE DEVELOPMENT IN PARTIALLY CRYSTALLINE POLYESTER FIBERS. INFLUENCE OF THE MECHANICAL STRESS - Velev, Valentin; Arhangelova, Nina; Nedeva, Daniela; Stoyanova, Zhenya; Popov, Anton (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
There are present results from high temperature uniaxial extension of partially crystalline poly (ethylene terephthalate) (PET) yarns. Effect of the applied to the samples tensile stress at isothermal conditions on the structural changes in the studied objects have been investigated. The structural analyses of the processed fibers were realized using differential scanning calorimetry (DSC).